Formulation, Characterization, and Total Phenolic Content of Moringa (Moringa oleifera L.) Leaf Extract Sunscreen Cream with Triethanolamine Base Comparison - Mahdiyyah, Ade Abiyyatun; Farkhani, Aulia; Esadini, Ayu Rana; Pratama, Deri Putra; Cahyadi, Salwa Nisrina; Rifkia, Via (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Moringa (Moringa oleifera L.) leaves contain secondary metabolites such as flavonoids, phenols, tannins, saponins, and alkaloids. The phenolic and flavonoid compounds show strong antioxidant activity that can neutralize free radicals and protect the skin from oxidative damage. Despite its known photoprotective potential, the use of Moringa leaf extract in stable sunscreen cream formulations is still limited. Moreover, the influence of extract and emulsifier (triethanolamine) concentrations on the cream’s physical properties and their relation to total phenolic content has not been well studied. This study aimed to develop and evaluate Moringa leaf extract-based sunscreen creams with extract concentrations of 1%, 1.5%, 2%, and 2.5%, and triethanolamine concentrations of 1% and 1.5%. Eight formulas were prepared and evaluated for organoleptic characteristics, spreadability, homogeneity, pH, viscosity, phase separation, and emulsion type. The total phenolic content was also determined using the Folin–Ciocalteu method. Results showed that increasing the concentration of extract and triethanolamine significantly affected the pH, spreadability, and viscosity of the cream (p < 0.05), while all remained within acceptable ranges for topical preparations. The total phenolic content increased proportionally with extract concentration, with Formula 8 (2.5% extract) showing the highest phenolic content of 25.12 mg GAE/g. These findings indicate that Moringa leaf extract has strong potential as a natural antioxidant and photoprotective agent for sunscreen cream formulations.